THE INFLUENCE OF FATHER INVOLVEMENT IN PARENTING AND EMOTIONAL REGULATION ON THE AGGRESSIVENESS OF AL MAKSUM PRIVATE MIDDLE SCHOOL STUDENTS - Muhammad Nur Habibie; Amanah Surbakti; Suaidah Lubis (RADJA PUBLIKA, 2023)
The phenomenon of aggressiveness has now developed and become a common problem in adolescents which is usually in the form of juvenile delinquency. Aggressive behavior of adolescents is certainly influenced by many factors. The research sample was 114 students of class VII and VIII of SMP Al Maksum. Data analysis technique using multiple linear regression analysis. The results showed that: (1) there was a negative and significant effect of father involvement in parenting on student aggressiveness (p = 0.000); (2) there is a negative and significant effect of emotion regulation on student aggressiveness p = 0.000); (3) there is a significant influence between father's involvement in parenting and emotional regulation simultaneously on the aggressiveness of SMP Al Maksum students..